Well-Being of Ambulatory Adults With Cerebral Palsy: Education, Employment, and Physical Function of a Cohort Who Received Specialized Pediatric Care - Shrader, M. Wade; Church, Chris; Lennon, Nancy; Shields, Thomas; Salazar-Torres, Jose J.; Howard, Jason J.; Miller, Freeman (Frontiers in Neurology, 2021)
Introduction: Transition from pediatric health care presents challenges for young adults with cerebral palsy (CP). The purpose of this project was to describe well-being by assessing education, employment, physical function, walking activity, and utilization of health care in an adult cohort with CP. Method: In this IRB-approved prospective study, we invited former patients from our tertiary care pediatric CP center to complete a set of patient-reported outcomes including PROMIS physical function and pain interference and a project-specific questionnaire about education, employment, independence, pain, satisfaction, and health care utilization. Participants wore a pedometer to monitor community walking activity. Chi-squared or t-tests were used to compare survey responses and walking activity data between three groups: participants who self-reported, reported by proxy, and normative data from age-matched non-disabled adults (NDA). Results: 126 adults with CP participated; 85 self-reported (age 29.7±4.3 years; GMFCS: I [28%], II [47%], III [25%]) and 41 reported proxy-reported (age 29.7±4.1; I [10%], II [68%], III [22%]). For the group who self-reported, high school graduation rate (99%) was similar to NDA (92%; p=0.0173) but bachelor’s degree achievement rate (55%) was higher than NDA (37%; p<0.001). Despite more advanced education, unemployment rate in this group was higher than NDA 33%. For the group who proxy-reported, educational levels (73% high school graduates, 0% bachelor’s degree) were lower (p<0.001) and unemployment was higher than NDA, at 64%. The cohort demonstrated lower physical function and less walking activity compared with NDA (p<0.001). This cohort of adults with CP reported significantly higher frequency of pain (48% vs 12% for NDA; p<0.001), but less pain interference with daily activities than NDA based on PROMIS results (p<0.001). This cohort had limited utilization of specialty care, specifically orthopedics (21%) and physical therapy (15%). Discussion: This cohort of adults with CP had similar levels of education as NDA but had high rates of unemployment. Although pain was frequent, impact on work and independent living did not exceed reports from NDA. Better targeted societal resources for adults with physical disabilities are urgently needed to allow equitable access to employment, promote opportunities for independence, and enable full participation in community life.